Myristoleic acid produced by enterococci reduces obesity through brown adipose tissue activation. Issue 7 (19th November 2019) - Quan, Lin-Hu; Zhang, Chuanhai; Dong, Meng; Jiang, Jun; Xu, Hongde; Yan, Chunlong; Liu, Xiaomeng; Zhou, Huiqiao; Zhang, Hanlin; Chen, Li; Zhong, Fei-Liang; Luo, Zhao-Bo; et al.
Abstract : Objective: Dietary fibre has beneficial effects on energy metabolism, and the majority of studies have focused on short-chain fatty acids produced by gut microbiota. Ginseng has been reported to aid in body weight management, however, its mechanism of action is not yet clear. In this study, we focused on the potential modulating effect of ginseng on gut microbiota, aiming to identify specific strains and their metabolites, especially long-chain fatty acids (LCFA), which mediate the anti-obesity effects of ginseng. Design: Db/db mice were gavaged with ginseng extract (GE) and the effects of GE on gut microbiota were evaluated using 16S rDNA-based high throughput sequencing. To confirm the candidate fatty acids, untargeted metabolomics analyses of the serum and medium samples were performed. Results: We demonstrated that GE can induce Enterococcus faecalis, which can produce an unsaturated LCFA, myristoleic acid (MA). Our results indicate that E. faecalis and its metabolite MA can reduce adiposity by brown adipose tissue (BAT) activation and beige fat formation. In addition, the gene of E. faecalis encoding Acyl-CoA thioesterases (ACOTs) exhibited the biosynthetic potential to synthesise MA, as knockdown (KD) of the ACOT gene by CRISPR-dCas9 significantly reduced MA production. Furthermore, exogenous treatment with KD E. faecalis could not reproduce the beneficial effects of wild type E. faecalis, which work by augmenting the circulating MA levels. Conclusions: Our results demonstrated that the gut microbiota-LCFA-BAT axis plays an important role in host metabolism, which may provide a strategic advantage for the next generation of anti-obesity drug development.